ISO/IEC 10646과 멀티바이트 코드 세트간의 변환시스템의 설계 및 구현 - 김철(Chul Kim) (한국정보전자통신기술학회 논문지, 2018)
In this paper, we designed and implemented a code conversion method between ISO/IEC 10646 and the multi-byte code set. The Universal Multiple-Octet Coded Character Set(UCS) provides codes for more than 65,000 characters, huge increase over ASCII's code capacity of 128 characters. It is applicable to the representation, transmission, interchange, processing, storage, input and presentation of the written form of the language throughout the world. Therefore, it is so important to guide on code conversion methods to their customers during customer systems are migrated to the environment which the UCS code system is used and/or the current code systems, i.e., ASCII PC code and EBCDIC host code, are used with the UCS together. Code conversion utility including the mapping table between the UCS and IBM new host code is shown for the purpose of the explanation of code conversion algorithm and its implementation in the system. The programs are successfully executed in the real system environments and so can be delivered to the customer during its migration stage from the UCS to the current IBM code system and vice versa. 본 논문에서는 ISO/IEC 10646과 멀티바이트 코드 세트간의 변환 시스템을 설계하고 구현한다. 65,000 문자의 코드를 제공하는 UCS 세트는 128 문자의 코드 용량을 제공하는 ASCII 코드의 제한성을 해결하고, 전세계 언어의 표현, 전송, 교환, 처리, 저장 및 입출력을 단일 코드 페이지에서 적용하며, 다국어 소프트웨어 개발시 코드 변환을 단순화시킴으로써 프로그램의 코드 수정을 위한 시간과 비용을 효율적으로 절감하게 한다. 따라서 UCS 코드 시스템과 ASCII 및 EBCDIC 코드 시스템들이 혼용되어 사용되는 환경에서는 상호 시스템간의 코드 변환 방법은 시스템 마이그레이션시 제공되어야 하는 중요한 고려 사항이다. 본 논문의 코드 변환 유틸리티는 UCS와 IBM 호스트 코드간의 매핑 테이블을 포함하고 있으며 제안된 코드 변환 알고리즘을 시스템에서 구현하였다. 제안된 코드 변환 프로그램은 실제 시스템 환경에서 성공적으로 구동하였음을 검증하였고, UCS와 멀티바이트 코드 시스템간의 마이그레이션시 가이드라인으로 제공될 수 있다.